Choline chloride based eutectic solvent: a highly efficient reaction media for the synthesis of 3,4-dihydropyrimidin-2(1H)-thiones - Malamiri, Fatemeh; Badri, Rashid; Khaksar , Samad; Salahshour, Peyman (Journal of Composites and Compounds, 2022)
A mild and green protocol was developed to the 3,4-dihydropyrimidin-2(1H)-thione derivatives preparation in deep eutectic solvent without the use of a catalyst or any other additive. The procedure offers a number of benefits, including clean reaction profile, avoiding the use of typical toxic catalysts, an easy workup procedure, short reaction times, and low prices.